A Multimodal Critical Discourse Analysis of “Garnier Sakura White” Advertisement - Marcella Pricilia; Ichwan Suyudi (ITScience (Information Technology and Science), 2023)
Television ads are one of the many types of mass media advertisements that inevitably surround people's lives today. It is a multimodal discourse in which the text consists of complex meaning resources. The objective of this research is to analyze the multimodality of the